Recent Trends in German and European Constitutional Law: German Reports Presented to the XVIIth International Congress on Comparative Law, Utrecht, 16 to 22 July 2006 - Riedel, Eibe (Springer-Verlag Berlin Heidelberg, 2006)
This volume contains the German National Reports on Public Law presented at the XVIIth Congress of the International Academy of Comparative Law, Utrecht 2006. The articles provide an overview over recent developments and new issues in both European Constitutional and German Public Law from a German perspective and offer an in-depth analysis of the legal issues discussed. The book offers scholars as well as practitioners a sound basis for studies on a wide range of current and interesting issues in the field of comparative law
Includes bibliographical references
Keywords: Konferenzschrift -- 2006 -- Utrecht; Europäische Union; Verfassungsrecht; Deutschland